2020
DOI: 10.1016/j.neurobiolaging.2019.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation, but not tau pathology, is independently associated with amyloid positivity and memory impairment

Abstract: We sought to determine if upstream amyloid accumulation and downstream cognitive impairment have independent relationships with microglial activation and tau pathology. Fifty-eight older adults were stratified by amyloid and cognitive status based on 18 F-florbetaben PET, history, and neuropsychological testing. Of these, 57 had 11 C-PBR28 PET to measure microglial activation and 43 had 18 F-MK-6240 PET to measure tau pathology. Amyloid and cognitive status were associated with increased overall binding for bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 50 publications
2
53
0
1
Order By: Relevance
“…Zou et al. showed that microglial activation assessed by [ 11 C]PBR28 is independently associated with amyloid load and memory impairment, but not with tau burden assessed by [ 18 F]florbetaben and [ 18 F]MK-6240, respectively, in patients with AD ( 74 ). Whereas Dani et al showed that [ 11 C]PBR28-measured microglial activation correlates with both tau and Aβ deposition assessed by [ 18 F]flortaucipir and [ 18 F]flutemetamol in patients with AD ( 69 ) ( Figures 2D, E ).…”
Section: Neuroinflammation Positron Emission Tomography Imagingmentioning
confidence: 99%
“…Zou et al. showed that microglial activation assessed by [ 11 C]PBR28 is independently associated with amyloid load and memory impairment, but not with tau burden assessed by [ 18 F]florbetaben and [ 18 F]MK-6240, respectively, in patients with AD ( 74 ). Whereas Dani et al showed that [ 11 C]PBR28-measured microglial activation correlates with both tau and Aβ deposition assessed by [ 18 F]flortaucipir and [ 18 F]flutemetamol in patients with AD ( 69 ) ( Figures 2D, E ).…”
Section: Neuroinflammation Positron Emission Tomography Imagingmentioning
confidence: 99%
“…20,21 Although AIF-free methods inherently introduce bias, several such studies have detected increased TSPO in various neurological disorders, with colocalization to abnormalities in other biomarkers. 22,23 In addition, AIF-free methods often reduce variance caused by inter-subject differences in physiological TSPO expression, thus improving power for statistical analysis. 21 Because binding behavior may differ among different radioligands and diseases, we recommend validating pseudo-reference methods against arterial sampling prior to their application.…”
Section: Overcoming Obstacles To Identifying Neuroinflammation Using Pet Imagingmentioning
confidence: 99%
“…49,50 The exact pathological stimulus for increased TSPO in AD remains unclear. Studies have observed increased TSPO binding in asymptomatic individuals with incidental amyloid positivity 23,51 and in participants meeting clinical criteria for amnestic MCI or mild AD with absence of amyloid binding on PET. 23,52 This suggests that TSPO may increase in response to both amyloid deposition and amyloid-independent neurodegeneration.…”
Section: Neurodegenerative Disorders 41 Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Our current study selected a subset participants from a pre-established research cohort. In a prior study of the larger cohort, both 18 F-MK-6240 and 11 C-PBR28 binding were greater in amyloid-positive than in amyloid-negative participants, specifically in neocortical regions for 11 C-PBR28 and in the medial temporal lobe for 18 F-MK-6240 [35]. In our sub-sample, we observed similar regional patterns of increased 11 C-PBR28 and 18 F-MK-6240 binding in association with lower UPSIT scores, suggesting that odor identification impairment may be mechanistically linked to inflammation and tau pathology, and not just a nonspecific measure of neurodegeneration.…”
Section: Discussionmentioning
confidence: 98%